Brane brick models for the Sasaki-Einstein 7-manifolds Y p,k (ℂℙ1 × ℂℙ1) and Y p,k (ℂℙ2) - Sebastián Franco; Dongwook Ghim; Rak-Kyeong Seong (Journal of High Energy Physics, 2023)
Abstract The 2d (0, 2) supersymmetric gauge theories corresponding to the classes of Y p,k (ℂℙ1 × ℂℙ1) and Y p,k (ℂℙ2) manifolds are identified. The complex cones over these Sasaki-Einstein 7-manifolds are non-compact toric Calabi-Yau 4-folds. These infinite families of geometries are the largest ones for Sasaki-Einstein 7-manifolds whose metrics, toric diagrams, and volume functions are known explicitly. This work therefore presents the largest list of 2d (0, 2) supersymmetric gauge theories corresponding to Calabi-Yau 4-folds with known metrics.